Contaminação por Toxocara spp. e Ancylostoma spp. em áreas de Lazer do Município de Canoinhas, SC - Pedrassani, Daniela [UNESP]; Viera, A. M.; Thiem, E. M.B. (My University, 2008)
Visceral and cutaneous larva migrans are zoonoses caused by the Toxocara spp. and Ancylostoma spp. respectively. The objective of this research was to evaluate the contamination for these agents in areas of leisure from the city of Canoinhas, Santa Catarina, by means of the techniques of spontaneous sedimentation, centrifugal sedimentation and centrifugal fluctuation. From the examined areas of leisure, 100% had disclosed the contaminated sand and 80% excrements contaminated by Ancylostoma spp and/ or Toxocara spp.. Of these, 100% had presented contamination for the Ancylostoma spp and only one presented contamination with eggs of Toxocara spp..The presence of Ancylostoma spp. and Toxocara spp. in the analyzed sand samples was of 39%. In the excrement examinations collected in the leisure areas 17% of positive samples had been detected, being detected only eggs of Ancylostoma spp. The study it demonstrated that the contamination of the areas of leisure of the Canoinhas city, is preoccupying, strengthening the necessity to implement measured effective for control of zoonoses in leisure areas.
Contamination by Toxocara spp. and Ancylostoma spp. in areas of leisure from Canoinhas County, Santa Catarina state
Keywords: Ancylostoma; Larva Migrans; Public health; Toxocara; Zoonose